Pengaruh Modal Sendiri Terhadap Omzet Penjualan Pada koperasi Mahasiswa “Almamater” Universitas Negeri Makassar - Abdul Hafid; Ilham Abu (Economy Deposit Journal (E-DJ), 2020)
The Makassar State University “alma mater” student cooperative is a cooperative engaged in the cadre field which includes entrepreneurship and entrepreneurship cadres which are expected to be able to direct the mindset of members who are more productive. The size of the cooperative business depends on the cooperative's ability to raise funds, both from their own capital and from loans. Capital has a role in efforts to increase cooperative business, with the cooperative's own capital, it can be used to increase cooperative business with the aim of increasing turnover in cooperatives. Based on preliminary observations of own capital, the student cooperative "alma mater" UNM, has increased as well as sales turnover although the amount of increase in sales turnover is not so large when compared to the previous year. This research aims to determine the effect of own capital on sales turnover in the UNM "alma mater" student cooperative. . This study uses a quantitative approach. The population in this study is data on own capital and sales turnover data for 5 years starting (2012-2016). Data collection methods are interviews and documentation. Methods of data analysis with simple linear regression analysis. The results showed that the equity in the UNM "alma mater" student cooperative had no significant effect on sales turnover. However, capital itself has a positive influence or impact in efforts to increase sales turnover in the UNM "alma mater" student cooperative.